Tingkat Literasi Digital dan Pengaruhnya terhadap Keterampilan Abad-21 Mahasiswa ditinjau dari Perspektif Gender - Adelia Alfama Zamista; May Shanda Charona (Cetta: Jurnal Ilmu Pendidikan, 2023)
The 21st century is known for its rapid technological developments, one of which is the development of digital technology. This digital technology has penetrated various fields, including education. This research aims examine the level of digital literacy and its influence on students' 21st century skills from a gender perspective. This research method is a quantitative method. The research population is active students of the Tadris Physics study program who are currently attending lectures in the first to fourth years. The research sample consisted of 38 students (19 male students and 19 female students), selected using the quota sampling technique. Data collection in this research was carried out using questionnaires and interviews. The research instruments are 2 main questionnaires that can gather information about students' digital literacy levels and students' achievement of 21st century skills. Data analysis was conducted by calculating the average score for students' digital literacy and 21st century skills based on gender. Furthermore, an analysis of the relationship between digital literacy and students' 21st century skills will also be carried out. The relationship between the two variables was analyzed using a simple regression test. The results of data analysis show that the level of digital literacy and 21st century abilities of students is in the “good” category. However, for both variables there are no significant differences between male and female students with the significance values ​​of the difference test results for digital literacy and 21st century skills being 0.125 and 0.747 respectively (both greater than 0.05). Furthermore, the results of the regression analysis revealed a statiscally significant positive influence of digital literacy on students' 21st century skills, with an F-value of 20.145 and a significance level of 0.000 < 0.05.